International Approaches to Regulation of Medicinal Products Containing Viable Human Cells - E. V. Melnikova; A. A. Goryaev; M. V. Savkina; O. V. Merkulova; A. A. Chaplenko; O. A. Rachinskaya; I. S. Semenova; G. A. Trusov; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The intensive development of cellular technologies stipulates the introduction at the global level of medicinal products based on viable human cells, which in most countries are referred to as biomedical cell products. The authors conducted a comparative analysis of the regulatory framework in different countries and determined special aspects of regulation of cell therapy products (analogues of biomedical cell products). Some countries have mechanisms for priority review of cell therapy products for marketing authorization, such as accelerated assessment, accelerated approval, or conditional marketing authorisation. These mechanisms are currently absent in Russia, because of the novelty of the regulatory framework, and the biological properties of innovative cell products. Biomedical cell products are regarded as a separate class of medicinal products in Russia, they are not treated as biologicals and are regulated by the Federal Law No. 180-FZ «On Biomedical Cell Products» of June 23, 2016. The main difference in regulation of cell-based products in the Russian Federation is the principle of unified requirements for marketing authorisation of autologous, allogeneic, and combined biomedical cellular products, and the absence of the «hospital exemptions» mechanism that exists in many countries. This mechanism allows prescription and use of personalised autologous medicines produced in the laboratory of a medical institution for a particular patient.